The effect of educational information about treatments for schizophrenia on stigmatizing perceptions. (September 2016) - Schlier, Björn; Lange, Pia; Wiese, Salome; Wirth, Anna; Lincoln, Tania
Abstract: Background: A promising strategy for reducing stigmatizing perceptions towards people with schizophrenia is education about treatment and recovery. The effects of different kinds of treatment information on stigmatizing perceptions, however, have yet to be compared directly. This study compared three different educational interventions focusing on medication, CBT, and psychodynamic psychotherapy in their potential to reduce stigmatizing perceptions towards people with schizophrenia. Methods: In an online experiment 178 participants received one of three psychoeducation texts that focused on medication, CBT or psychodynamic therapy. The effects on stereotypical beliefs about psychosis (dangerousness, unpredictability, blame, prognostic pessimism) and emotional responses towards people with schizophrenia (anxiety, anger, sympathy) were tested. Results: Perceptions of dangerousness, unpredictability, and anxiety towards people with schizophrenia were reduced in all conditions. Prognostic pessimism was reduced only after reading the CBT information. Limitations: No neutral control group was included. The sample was not representative with respect to level of education or gender. Conclusions: Stigmatizing perceptions may be reduced by receiving information about any type of treatment for psychosis and without producing negative side-effects, although this needs to be replicated in a controlled study. However, information on CBT seems most suitable to reduce stigma, since it was able to reduce prognostic pessimism. Highlights: Public stigma of schizophrenia can be reduced by informing about treatment. All treatment information reduces the perceived dangerousness, unpredictability and blame. No facet of stigma was increased by providing treatment information. Only information on CBT specifically reduced prognostic pessimism.